SERPINA1 mRNA as a Treatment for Alpha-1 Antitrypsin Deficiency - Brendan Connolly; Cleo Isaacs; Lei Cheng; Kirtika H. Asrani; Romesh R. Subramanian (Journal of Nucleic Acids)
Alpha-1-antitrypsin (AAT) deficiency is a genetic disorder that produces inactive/defective AAT due to mutations in the SERPINA1 gene encoding AAT. This disease is associated with decreased activity of AAT in the lungs and deposition of excessive defective AAT protein in the liver. Currently there is no specific treatment for liver disease associated with AAT deficiency. AAT lung disease is often treated with one of several serum protein replacement products; however, long-term studies of the effectiveness of SerpinA1 replacement therapy are not available, and it does not reduce liver damage in AAT deficiency. mRNA therapy could potentially target both the liver and lungs of AAT deficient patients. AAT patient fibroblasts and AAT patient fibroblast-derived hepatocytes were transfected with SERPINA1-encoding mRNA and cell culture media were tested for SerpinA1 expression. Our data demonstrates increased SerpinA1 protein in culture media from treated AAT patient fibroblasts and AAT patient fibroblast-derived hepatocytes. In vivo studies in wild type mice demonstrate SERPINA1 mRNA biodistribution in liver and lungs, as well as SerpinA1 protein expression in these two target organs which are critically affected in AAT deficiency. Taken together, our data suggests that SerpinA1 mRNA therapy has the potential to benefit patients suffering from AAT deficiency.